1974
DOI: 10.1126/science.183.4121.220
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine Uptake into Cerebral Cortical Synaptosomes after One Fight or Electroconvulsive Shock

Abstract: Membrane affinity for the neurotransmitter norepinephrine is rapidly but reversibly decreased in nerve terminals of the cerebral cortex by intense nervous stimulation. This should adaptively facilitate alerting during acute emergency and stress. The Michaelis constant (K(m)) for the high-affinity active uptake of norepinephrine into crude synaptosome-rich homogenates of the cerebral cortices of mice was increased 68 percent after 15 minutes of intense fighting and 110 percent 5 minutes after a single electroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…More recently, chronic subordination stress in tree shrews was found to persistently upregulate alpha 2C receptors in discrete brain stem nuclei, but not in the locus coeruleus or prefrontal cortex (Flügge et al, 1997, 2003). Such findings need to be seen in the context of similar observations in animals that engaged in attack behavior (Welch et al, 1974; Tizabi et al, 1980) and point to a much more general role of noradrenergic activity during social conflict that is not specific to defeat. It will be instructive to learn how activation of norepinephrine and its receptor and transporter molecules are linked with a specific type of social stress, and how this noradrenergic activity is coordinated with those of excitatory amino acids and other amines and peptides.…”
Section: Neurobiological Characteristics Therapeutics and Drug Abusementioning
confidence: 71%
“…More recently, chronic subordination stress in tree shrews was found to persistently upregulate alpha 2C receptors in discrete brain stem nuclei, but not in the locus coeruleus or prefrontal cortex (Flügge et al, 1997, 2003). Such findings need to be seen in the context of similar observations in animals that engaged in attack behavior (Welch et al, 1974; Tizabi et al, 1980) and point to a much more general role of noradrenergic activity during social conflict that is not specific to defeat. It will be instructive to learn how activation of norepinephrine and its receptor and transporter molecules are linked with a specific type of social stress, and how this noradrenergic activity is coordinated with those of excitatory amino acids and other amines and peptides.…”
Section: Neurobiological Characteristics Therapeutics and Drug Abusementioning
confidence: 71%
“…Evidence of arousal homeostasis compensating for altered levels of sensory input has also been obtained. At the synaptic level, norepinephrine uptake into cortical synaptosomes is altered by fighting in such a manner as to result in arousal homeostasis (Hendley, Moisset, & Welch, 1973;Welch, Hendley, & Turek, 1974). Electrophysiologically, a number of animal studies (reviewed by Zubeck, 1969) have demonstrated a slowing of cortical EEG rhythms, similar to those observed in sensorily deprived humans, following visual, auditory, or olfactory deafferentation.…”
Section: Evidence For An Arousal Theorymentioning
confidence: 99%
“…Even before their cloning, neuroscientists speculated that the regulation of neurotransmitter transporter expression and function could contribute to the plasticity characteristic of neuronal synapses, contributing ultimately to changes in behavior [52, 84, 85]. The availability of molecular tools in the early 1990s provided opportunities to put these speculations to the test [2].…”
Section: Introductionmentioning
confidence: 99%